Dalea bicolor: An alternative for the treatment of bacteria of public health importance - Morales-Ubaldo, Yesica Anayanci (2022)
The aim of this study was to determine the in vitro antibacterial activity of the hydroalcoholic extract of Dalea bicolor on bacteria of importance in public health. The antibacterial activity was determined by the Minimum Inhibitory Concentration (MIC) and the Minimum Bactericidal Concentration (MBC). It was determined that the hydroalcoholic extract of Dalea bicolor has inhibitory activity at concentrations of 3.12 to 12.5 mg/ml and bactericidal activity at 50 and 100 mg/ml and can be considered as an alternative for the treatment of infections associated with bacteria of importance in public health.